Brief Annual Plan and Tsunami Rehabilitation Plan - Planning Commission (Planning Commission, 2010)
Andaman & Nicobar Group of Islands comprises 572 islands with a total geographical area of 8249 sq. kms., of which 38 are inhabited. About 86% of the land is covered by forests and only 5.62% is revenue land. The Islands maintain communication with the mainland through Kolkata, Chennai and Vishkhapatnam Ports. The Andaman group stretches over 467 kms in length with a maximum breadth of 52 kms and Nicobar group stretches over 259 kms in length with a maximum breadth of 58 kms. The Andaman and Nicobar Islands is stretched over 750 kms from North to South.
Andaman and Nicobar Islands